Bargaining and contribution games with deadlines - Yu, Zhixian (2018)
This thesis considers play in bargaining games subject to Endogenous Commitment and in contribution games with a sunk cost. In bargaining games, Endogenous Commitment (EC) describes a common feature in negotiation: once an offer is made, neither would the proposer offer nor would the respondent accept anything worse. Similarly, in contribution games, the notion of sunk cost implies an irrevocability similar to EC: it is impossible for either contributor to reduce his or her contribution, so far as the cost is sunk. Another similarity between the bargaining and contribution games in our thesis is that we assume (most of) them to be finite, meaning that there is a deadline effect: when approaching the deadline, the final negotiator/contributor has a stronger incentive to reach an agreement/complete the project. The deadline effect puts the final negotiator/contributor in a relatively weaker position. With these two similarities, the bargaining and contribution games in our thesis share some similar features.